Pesantren Aceh sebagai Wujud Menciptakan Perdamaian - Hayani, Aida; Sa'diyah, Miftahus; Hadi, Khairul (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2020)
AbstrakAccording to the majority religious groups, in truth, always give priority boarding to the authority ta’dzim culture and a religious teacher Tgk, the more their binding normative frame, such as the doctrine of al-Muta’alim Ta’lim book, which does not allow the conflict in it. However, that happens, the social dynamics of schools that still apply the system of management of the potential sources based on a figure of clerics (as a role model at the same time policy makers), is actually very vulnerable to grow a conflict. As is the case in traditional Islamic boarding schools and semi-modern, conflicts occur, especially when the clerics who plays as the founder and owner of boarding dies, or when the pesantren, the founder or the resume, the teachers, caregivers, or also the family become involved in affairs outside of schools, for example, state, politics and others. By using descriptive analysis method with dispute resolution theory, then, is clearly visible how the settlement of conflict resolution in schools are often taken with unique ways, including through intermarriage boarding, istighotsah, haul and akhirussanah. By stage of conflict resolution through the streets silaturrahmi as a process of conflict prevention, bahtsul matsa’il as the emphasis and peyekatan conflict, Tabayun as the process of setting and managing conflict and reconciliation as the final process of conflict resolutionKeyword: Pesantren, Perdamaian , Aceh